Relationship between intestinal microbiota and ulcerative colitis: Mechanisms and clinical application of probiotics and fecal microbiota transplantation - Shen, Zhao-Hua; Zhu, Chang-Xin; Quan, Yong-Sheng; Yang, Zhen-Yu; Wu, Shuai; Luo, Wei-Wei; Tan, Bei; Wang, Xiao-Yan (World journal of gastroenterology : WJG, 2018)
Ulcerative colitis (UC) is an inflammatory disease that mainly affects the colon and rectum. It is believed that genetic factors, host immune system disorders, intestinal microbiota dysbiosis, and environmental factors contribute to the pathogenesis of UC. However, studies on the role of intestinal microbiota in the pathogenesis of UC have been inconclusive. Studies have shown that probiotics improve intestinal mucosa barrier function and immune system function and promote secretion of anti-inflammatory factors, thereby inhibiting the growth of harmful bacteria in the intestine. Fecal microbiota transplantation (FMT) can reduce bowel permeability and thus the severity of disease by increasing the production of short-chain fatty acids, especially butyrate, which help maintain the integrity of the epithelial barrier. FMT can also restore immune dysbiosis by inhibiting Th1 differentiation, activity of T cells, leukocyte adhesion, and production of inflammatory factors. Probiotics and FMT are being increasingly used to treat UC, but their use is controversial because of uncertain efficacy. Here, we briefly review the role of intestinal microbiota in the pathogenesis and treatment of UC.